2011
DOI: 10.1186/cc10545
|View full text |Cite
|
Sign up to set email alerts
|

Duration of antibiotic therapy for bacteremia: a systematic review and meta-analysis

Abstract: IntroductionThe optimal duration of antibiotic therapy for bloodstream infections is unknown. Shorter durations of therapy have been demonstrated to be as effective as longer durations for many common infections; similar findings in bacteremia could enable hospitals to reduce antibiotic utilization, adverse events, resistance and costs.MethodsA search of the MEDLINE, EMBASE and COCHRANE databases was conducted for the years 1947-2010. Controlled trials were identified that randomized patients to shorter versus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
126
0
7

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 159 publications
(140 citation statements)
references
References 59 publications
7
126
0
7
Order By: Relevance
“…Similar results on de-escalation strategies were delivered by the studies of Turza and Havey et al [147,148]. Neither clinical and microbiologic recovery, nor survival were negatively influenced by a shorter treatment duration compared to groups with longer therapy.…”
Section: Treatment Duration and Treatment Managementsupporting
confidence: 73%
“…Similar results on de-escalation strategies were delivered by the studies of Turza and Havey et al [147,148]. Neither clinical and microbiologic recovery, nor survival were negatively influenced by a shorter treatment duration compared to groups with longer therapy.…”
Section: Treatment Duration and Treatment Managementsupporting
confidence: 73%
“…There was no similar study in this regard, but in a study, which had evaluated the effect of antibiotic therapy on final clinical results in patients with bacteremia, the results showed that the lengthening the time of antibiotic therapy makes no significant difference on clinical results (Havey et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…We selected a cut-off of more than 7 days of treatment based on evidence that most bacterial infections can be treated with a duration of 7 days or less of antibiotics. 6,[34][35][36][37][38] We considered consecutive prescriptions for the same antibiotic to be part of the same treatment course if the drug was prescribed by the same physician, to the same patient and there was no more than 3 days between prescriptions.…”
Section: Prescribing Tendencies For Antibioticsmentioning
confidence: 99%